Implementation of Village Fund Utilization Policy in Supporting Autonomy of Oefafi Village in East Kupang District, Kupang Regency - East Nusa Tenggara Province - William Djani; Jeni Jacoba Therik; Eliza Margaretha Mbatu (The ES Accounting And Finance, 2022)
The objective of this study is to provide clarity on several things to realize the objectives of implementing the policy on the use of village funds, and therefore the research team conducted a study of the theory and concept of policy implementation as one of the areas of study for public policy. The goal is that this perspective can direct the focus of research on a research framework and analysis that is appropriate, relevant, applicable, measurable with a methodology that can be scientifically justified. The results showed that the process of implementing programs funded by village funds helped Oefafi village to develop its village. However, the regional and village governments certainly have a number of limitations in improving the implementation aspects of village fund utilization policies to support village autonomy in a sustainable manner. The results of the study show that the variables of policy implementation in the use of village funds are still not running optimally and require serious attention from parties related to the management of Oefafi village funds and need to be derived as new concepts of public policy implementation based on the social context so that in the end they are able to provide concrete contribution to the achievement of the village development program strategy. Therefore, the recommendations put forward in this study are that it is necessary to achieve policy goals as the final target that requires attention and support from resources, communication, implementing attitudes, bureaucratic structures, conducive environmental aspects, policy measures and objectives to determine the success of the policy implementation process.